Multi-layer co-extrusion one-step molding self-adhesion ultrathin foaming foam adhesive tape and preparation method thereof

Through multi-layer co-extrusion and single-molded self-adhesive ultra-thin foam foam tape, the thickness and pollution problems of traditional foam tape are solved, and an ultra-thin, efficient and environmentally friendly production process is achieved.

CN119875523APending Publication Date: 2025-04-25FELKER FUNCTIONAL MATERIALS (SHANGHAI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510122607.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Traditional foam tape is difficult to achieve a thickness of less than 110um, takes up a large space, and requires composite double-sided tape and release paper, so residual pollution is difficult to clean after use.

Method used

Multi-layer coextrusion single-molded self-adhesive ultra-thin foam foam tape, including anti-static ionization layer, foam layer, bonding layer and adhesive layer, is prepared by four-layer coextrusion integrated rotary film blowing equipment, reducing complex coating and release paper treatment.

Benefits of technology

It achieves an ultra-thin 110um thickness, simplifies the production process, avoids residual pollution, has obvious cost advantages, and can add functional masterbatches to the formula to flexibly adjust the formula.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875523A_ABST
    Figure CN119875523A_ABST
Patent Text Reader

Abstract

The invention discloses a multi-layer co-extrusion one-step molding self-adhesive ultrathin foaming foam adhesive tape which comprises an antistatic release layer, a foaming layer, a bonding layer and an adhesive layer, and the antistatic release layer, the foaming layer and the bonding layer are collectively called as base material layers; the antistatic release layer is prepared from LDPE (Low-Density Polyethylene), Exfin and antistatic master batches; the foaming layer is composed of LLDPE (Linear Low Density Polyethylene), LDPE (Low Density Polyethylene), rim charge and foaming master batch; the bonding layer is prepared from LDPE (Low-Density Polyethylene) and SEBS (Styrene The adhesive layer is composed of SEBS, tackifying resin, white oil, fumed silica and an antioxidant. A one-time forming method is adopted, and master batches coated with active gas in advance are adopted, so that the use is simpler and safer. And a multi-layer co-extrusion one-step forming method is adopted, so that the subsequent coating procedure is reduced, the cost is lower, and the method is more environment-friendly. By adopting the film blowing machine with a special structure, the ultrathin foam tape with flexible width size can be obtained, and the foam tape is more convenient to protect in the fields of electronic components and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of protective films, and in particular to a multi-layer co-extruded one-step self-adhesive ultra-thin foamed cotton tape and a preparation method thereof. Background Art

[0002] Foam tape is made of EVA or PE foam as the base material, coated with solvent-based (or hot-melt) pressure-sensitive adhesive on one or both sides, and then covered with release paper.

[0003] Its characteristics include good sealing and shock absorption effects, excellent sealing, resistance to compression deformation, flame retardancy, wettability, etc.; it can be used at a variety of temperatures (from minus ten degrees to dozens of degrees above zero) without affecting the effect; it has excellent properties such as strong durability, high temperature resistance and waterproofness.

[0004] It has a wide range of uses. In industry, it is often used in the packaging and transportation of electronic products, various small household appliances, mechanical parts, industrial instruments, auto parts, audio-visual equipment and other products, to increase cushioning, shock resistance and shock absorption, as well as sealing, to prevent products from being damaged due to high temperature, humidity, vibration, etc. during transportation; in daily life, it can be used to paste couplets, hooks, decorative stickers, paper, lightweight KT boards, small wooden boards, etc.; it is also commonly used in handicrafts; it is also suitable for the electronics industry, furniture industry, metal oil painting mirrors, car interior decoration logos, brand-name accessories and other aspects of pasting.

[0005] Traditional foam tapes generally use gas to fill the extruder to achieve continuous foaming, or mix the foaming material with the foaming agent and inject it into the mold to form, and then roll or cut it into shape. It is currently difficult for such products to achieve a thickness of 110um or even less, and they occupy a large space in some microelectronic products. In addition, traditional foams need to be compounded with double-sided tape or coated with glue to achieve adhesion, and need to be compounded with release paper to achieve unrolling and use. The compounded double-sided tape is often left on the protected surface after being torn off after use, causing pollution and the pollution is difficult to clean

[0006] Therefore, how to provide a multi-layer co-extruded one-step self-adhesive ultra-thin foam cotton tape and a preparation method thereof to solve the problems existing in the prior art is of great significance for its application. Summary of the invention

[0007] In view of this, the purpose of the present application is to provide a multi-layer co-extruded one-step molded self-adhesive ultra-thin foam cotton tape and a preparation method thereof, so as to solve the problem that the traditional protective film has obvious shortcomings.

[0008] To achieve the above object, the present invention provides the following technical solution: a multi-layer co-extruded one-step self-adhesive ultra-thin foamed cotton tape, comprising an antistatic release layer, a foaming layer, a bonding layer and an adhesive layer, wherein the antistatic release layer, the foaming layer and the bonding layer are collectively referred to as a substrate layer;

[0009] The antistatic release layer is composed of LDPE, Exfo la, and antistatic masterbatch;

[0010] The foaming layer is composed of LLDPE, LDPE, edge material and foaming masterbatch;

[0011] The bonding layer is composed of LDPE and SEBS;

[0012] The adhesive layer consists of SEBS, tackifying resin, white oil, fumed silica and antioxidant.

[0013] Preferably, the component ratio of the antistatic release layer is: 85% LDPE, 10% Exfo la, and 5% antistatic masterbatch;

[0014] The component ratio of the foaming layer is: 65% LLDPE, 20% LDPE, 10% edge material, and 5% foaming masterbatch;

[0015] The component ratio of the bonding layer is: 95% LDPE and 5% SEBS.

[0016] Preferably, the component ratio of the adhesive layer is: 30 components of SEBS, 40-60 components of tackifying resin, 10-20 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant.

[0017] Preferably, the particle size of the foaming masterbatch is 28-40 μm, the starting temperature is 165-175°C, and the maximum temperature is 215-225°C.

[0018] A method for preparing a multi-layer co-extruded one-step self-adhesive ultra-thin foam cotton tape, wherein all the formula materials of the adhesive layer are made into granules in advance by a granulator, a double-stage underwater granulation system is used, and different weight loss scale systems are used for each component.

[0019] Preferably, the white oil is added by a special liquid scale and injected into the screw at the second heating zone, and the remaining materials are conventionally discharged at the first discharge port.

[0020] Preferably, the components of the adhesive layer are prepared in advance as an adhesive layer masterbatch, and the equipment required for preparing the adhesive layer masterbatch includes a first granulator, a double cone feeder, and a second granulator;

[0021] The preparation method of the adhesive masterbatch comprises the following steps:

[0022] S1): 30 components of SEBS, 40-60 components of tackifying resin, 10-20 components of white oil, 0.5 components of fumed silica, and 0.5 components of antioxidant are put into use in a first granulator at a granulation temperature of 120-160 degrees to prepare a semi-finished tack layer masterbatch;

[0023] S2): The semi-finished adhesive masterbatch obtained in S1 is put into a double cone feeder, and the double cone feeder side force feeding method is used to vertically feed the discharge port of the double cone feeder into the feed port of the second single screw granulator at 90 degrees;

[0024] S3): Use the second granulator with a screw temperature of 80-100 degrees to prepare the sticky masterbatch, and the remaining 0.5 component of fumed silica is sprinkled on the molded particles as an anti-sticking release agent to prevent adhesion.

[0025] Preferably, the first granulator is a co-rotating three-screw device with a length-to-diameter ratio greater than 68; the second granulator is preferably a "high compression ratio" machine with a single screw diameter greater than 100 mm and a length-to-diameter ratio greater than 48.

[0026] Preferably, the first granulator adopts a first-stage natural exhaust method, a second-stage vacuum pumping method to treat volatiles, and a second-stage natural exhaust method to form.

[0027] Preferably, the foam tape is prepared using a four-layer co-extrusion integral rotary film blowing device, which includes a die head, an extruder, a winding mechanism, a thickness gauge, a cooling roller, an annealing rack, an infrared heating mechanism, a side material winding mechanism, a traction mechanism, a trimming mechanism, a herringbone frame, a foam stabilizing frame, and a five-layer frame, wherein the five-layer frame is divided into a bottom layer, a first layer, a second layer, a third layer, and a fourth layer;

[0028] There are four extruders, which are divided into ABCD extruders. The die head is installed in the middle of the bottom layer, and the four extruders are installed around the bottom layer. The discharge end of the extruder is connected to the feed end of the die head, the winding mechanism is installed on both sides of the first layer, the thickness gauge is installed on both sides of the second layer, the bubble stabilizing frame is installed in the middle of the second layer, the annealing frame and the winding mechanism are installed on both sides of the third layer, the traction mechanism and the herringbone frame are installed in the middle of the third layer, the trimming mechanism and the edge material winding mechanism are installed in the middle of the fourth layer, and the infrared heating mechanism is installed on both sides of the fourth layer.

[0029] Preferably, the adhesive layer masterbatch is added to a single-screw mold machine and extruded into a film at a temperature of about 100-120 degrees. The raw materials of the antistatic release layer, foaming layer, and bonding layer are respectively put into the corresponding ABC extruder for extrusion into a film. The processing temperature is 190 degrees, and the film frost line height is 50-120cm. By adjusting the screw speed, composite extrusion is carried out at a ratio of 20% for the adhesive layer and 80% for the substrate layer. After hot air shaping, a 110um thick thin film self-adhesive tape is made.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The equipment and process used in the present invention is based on the existing multi-layer co-extrusion self-adhesive film blowing equipment on the market. A small amount of two process equipment can meet the production needs;

[0032] 2. The one-step forming method designed by the present invention does not require re-coating or composite release paper, and has a simple process and great cost advantages;

[0033] 3. The ultra-thin foam tape produced by the present invention can also be added with color masterbatch, flame retardant masterbatch and other functional masterbatch in the multi-layer formula, and the formula can be adjusted flexibly.

[0034] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application so that it can be implemented in accordance with the contents of the specification, and to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the following is a detailed description of the preferred embodiments of the present application in conjunction with the accompanying drawings as follows.

[0035] Based on the detailed description of the specific embodiments of the present application in combination with the accompanying drawings below, those skilled in the art will become more aware of the above and other objects, advantages and features of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can also be obtained based on these drawings without creative work. In all drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale.

[0037] Figure 1 This is a composition table of the substrate layer of the present invention.

[0038] Figure 2 This is a table of embodiments of the adhesive layer of the present invention;

[0039] Figure 3It is a layered diagram of the present invention;

[0040] Figure 4 is a micrograph of the foaming layer in the present invention;

[0041] Figure 5 It is a structural diagram of the four-layer co-extrusion integral rotary film blowing equipment in the present invention;

[0042] Figure 6 This is a test result diagram of the adhesive layer in the present invention.

[0043] In the figure: 1. die head; 2. extruder; 3. winding mechanism; 4. thickness gauge; 5. cooling roller; 6. annealing rack; 7. infrared heating mechanism; 8. edge material winding mechanism; 9. traction mechanism; 10. edge trimming mechanism; 11. herringbone frame; 12. bubble stabilizing frame. DETAILED DESCRIPTION

[0044] To make the purpose, technical scheme and advantages of the embodiment of the present application clearer, the technical scheme in the embodiment of the present application will be clearly and completely described below in conjunction with the accompanying drawings in the embodiment of the present application. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all of the embodiments. In the following description, specific details such as specific configuration and components are provided only to help fully understand the embodiments of the present application. Therefore, it should be clear to those skilled in the art that various changes and modifications can be made to the embodiments described herein without departing from the scope and spirit of the present application. In addition, for clarity and brevity, the description of known functions and structures is omitted in the embodiment.

[0045] In addition, the present application may repeat reference numerals and / or letters in different examples. This repetition is for the purpose of simplicity and clarity, and does not in itself indicate the relationship between the various embodiments and / or settings discussed.

[0046] The term "and / or" in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, B exists alone, and A and B exist at the same time. The term " / and" in this article describes another type of association object relationship, indicating that there can be two relationships. For example, A / and B can mean: A exists alone, and A and B exist alone. In addition, the character " / " in this article generally indicates that the previous and next associated objects are in an "or" relationship.

[0047] It should also be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusions.

[0048] See also Figure 1-4 The present invention provides a multi-layer co-extruded one-step self-adhesive ultra-thin foam cotton tape and a technical solution for its preparation method:

[0049] 1. Selection of adhesive layer;

[0050] Adhesive Example 1: 30 components of SEBS, 40 components of tackifying resin, 10 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0051] Adhesive Example 2: 30 components of SEBS, 50 components of tackifying resin, 10 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0052] Adhesive Example 3: 30 components of SEBS, 60 components of tackifying resin, 10 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0053] Adhesive Example 4: 30 components of SEBS, 40 components of tackifying resin, 15 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0054] Adhesive Example 5: 30 components of SEBS, 50 components of tackifying resin, 15 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0055] Adhesive Example 6: 30 components of SEBS, 60 components of tackifying resin, 15 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0056] Adhesive Example 7: 30 components of SEBS, 40 components of tackifying resin, 20 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0057] Adhesive Example 8: 30 components of SEBS, 50 components of tackifying resin, 20 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0058] Adhesive Example 9: 30 components of SEBS, 60 components of tackifying resin, 20 components of white oil, 1 component of fumed silica, and 0.5 components of antioxidant;

[0059] The selection of each component is as follows:

[0060] SEBS is S6645; tackifying resin is Henghe HM900; fumed silica is Evonik A380; antioxidant 1010 is BASF.

[0061] The various adhesive components are weighed and granulated, and then different proportions of adhesive layer masterbatch are installed to obtain different adhesive layers. The granulation process is as follows:

[0062] S1): 30 components of SEBS, 40-60 components of tackifying resin, 10-20 components of white oil, 0.5 components of fumed silica, and 0.5 components of antioxidant are put into use in a first granulator at a granulation temperature of 120-160 degrees to prepare a semi-finished tack layer masterbatch;

[0063] S2): The semi-finished adhesive masterbatch obtained in S1 is put into a double cone feeder, and the double cone feeder side force feeding method is used to vertically feed the discharge port of the double cone feeder into the feed port of the second single screw granulator at 90 degrees;

[0064] S3): Use the second granulator with a screw temperature of 80-100 degrees to prepare the sticky masterbatch, and the remaining 0.5 component of fumed silica is sprinkled on the molded particles as an anti-sticking release agent to prevent adhesion.

[0065] The first granulator is preferably a co-rotating three-screw device with an aspect ratio greater than 68; the second granulator is preferably a "high compression ratio" machine with a single screw diameter greater than 100 mm and an aspect ratio greater than 48.

[0066] The first granulator adopts the method of natural exhaust in the first stage and vacuum extraction in the second stage to treat volatiles, and the second stage adopts the method of natural exhaust to form.

[0067] The foam tape is prepared using a four-layer film-forming equipment, which includes a die head 1, an extruder 2, a winding mechanism 3, a thickness gauge 4, a cooling roller 5, an annealing frame 6, an infrared heating mechanism 7, an edge material winding mechanism 8, a traction mechanism 9, a trimming mechanism 10, a herringbone frame 11, a foam stabilizing frame 12 and a five-layer frame. The five-layer frame is divided into a bottom layer, a first layer, a second layer, a third layer, and a fourth layer; the first layer, the second layer, the third layer, and the fourth layer can rotate as a whole.

[0068] There are four extruders 2, which are divided into ABC extruders. The die head 1 is installed in the middle of the bottom layer, and four extruders 2 are installed around the bottom layer. The discharge end of the extruder 2 is connected to the feed end of the die head 1, the winding mechanism 3 is installed on both sides of the first layer, the thickness gauge 4 is installed on both sides of the second layer, the bubble stabilizing frame 12 is installed in the middle of the second layer, the annealing frame 6 and the winding mechanism 3 are installed on both sides of the third layer, the traction mechanism 9 and the herringbone frame 11 are installed in the middle of the third layer, the trimming mechanism 10 and the edge material winding mechanism 8 are installed in the middle of the fourth layer, and the infrared heating mechanism 7 is installed on both sides of the fourth layer.

[0069] The substrate layer is produced according to the component ratio of the antistatic release layer: 85% LDPE, 10% Exfo la, and 5% antistatic masterbatch; the component ratio of the foaming layer is: 65% LLDPE, 20% LDPE, 10% edge material, and 5% foaming masterbatch; the component ratio of the bonding layer is: 95% LDPE and 5% SEBS. The antistatic release layer raw material, the foaming layer raw material, the bonding layer raw material, and the bonding layer masterbatch are respectively put into four screw extruders ABCD of a four-layer co-extrusion integral rotary film blowing equipment for blown film forming. After the film bubble rises, it is cut by a trimming mechanism 10, and then the foaming layer in the film is further heated and foamed by an infrared heating mechanism 7. After the foaming is completed, it enters the annealing rack 6 for annealing, and then after being shaped by a cooling roller 5, the thickness is measured by a thickness gauge 4. After the thickness measurement is completed, it is rolled up by a winding mechanism 3, and tested after being left to stand for 72 hours for aging and stabilization.

[0070] The annealing rack 6 heats the roller surface of the annealing roller by hot blowing, and the heated annealing roller contacts the film, thereby annealing the film.

[0071] The test items include: unfolding force, initial adhesion, adhesion after high temperature, contamination, and film curling test.

[0072] 1. Expanding force

[0073] The surface protection films were respectively wound on PP tube cores with an inner diameter of 3 inches to make film rolls with a width of 50 mm. According to JI SZ0237, the surface protection films were unwound from the film rolls at an unwinding speed of 20 m / min, and the high-speed unwinding force was measured. The test value is the unfolding force.

[0074] Internal standard: The evaluation of the unfolding force within 3N / 50mm is A, the evaluation of more than 3N / mm but not more than 7N / 50mm is B, and the evaluation of more than 7N / 50mm is C;

[0075] 2. Initial adhesion

[0076] The surface protective film was laminated 72 hours after it was made. The ultra-mirror steel plate was used as the test plate. The surface sand particle size was 0.02um. It was cut into a test plate of 15cmX5cm. The lamination conditions were at room temperature of 23 degrees and relative humidity of 50%. A 2kg rubber roller was used to laminate at a speed of 300mm / min. After being placed in this state for 30 minutes, the 180-degree peel strength of 25mm width was tested at a speed of 300mm / min according to JIS Z0237. The peel strength at this time is taken as the initial adhesion;

[0077] 3. Adhesion after high temperature

[0078] The surface protective film was laminated 72 hours after it was made. The ultra-mirror steel plate was used as the test plate. The surface sand particle size was 0.02um. It was cut into 15cmX5cm test plates. The lamination conditions were at room temperature of 23 degrees and relative humidity of 50%. A 2kg rubber roller was used to laminate at a speed of 300mm / min. After being placed in this state for 30 minutes, the laminated product was placed in a 50-degree temperature environment for 30 minutes for baking. After baking, it was taken out and left to stand for 30 minutes. Then, the 180-degree peel strength of 25mm width was tested at a speed of 300mm / min according to JIS Z0237. The peel strength at this time is used as the adhesion after high temperature;

[0079] 4. Layered testing (internal testing method);

[0080] 1. Stick the tape to the smooth steel plate, and test the 180-degree peel strength of 25 mm width at a speed of 300 mm / min according to JIS Z0237 to observe whether there is debonding / delamination on the surface;

[0081] 5. Pollution

[0082] After peeling off the sample film from the adhered object, spotlight the adhered surface in a dark room and observe the surface contamination status with the naked eye. The status is determined as follows: no contamination A, slight contamination B, contamination C;

[0083] 6. Film curling degree test

[0084] After bonding, the product was cut into the size of A4 paper with a blade. At room temperature and after high temperature, the bonded product was placed on the glass table. After standing for 30 minutes, the distance from the edge to the table was measured. The judgment results were: A for warping less than 1cm, B for warping greater than 1cm but less than 3cm, and C for warping greater than 3cm.

[0085] Test results:

[0086] (1) Room temperature peel strength test results for adhesive examples 1-9 are:

[0087] 11.5N / 25mm, 13N / 25mm, 13.5N / 25mm, 12.7N / 25mm, 13.7N / 25mm, 14.2N / 25mm, 13.7N / 25mm, 14.1N / 25mm, 14.8N / 25mm;

[0088] The peeling force test results of extruder (2) after high temperature are as follows:

[0089] 14N / 25mm, 14.2N / 25mm, 14.7N / 25mm, 13.8N / 25mm, 14.1N / 25mm, 14.6N / 25mm, 14.2N / 25mm, 14.3N / 25mm, 15.2N / 25mm;

[0090] Extruder (2) Delamination test results: Adhesive examples 1-9 can be torn apart completely;

[0091] Thickness gauge (4) Contamination test results: Adhesion examples 1-9 are all A.

[0092] The curling test results of the cooling roller (5) are as follows: Grade A: sticking to examples 2, 3, 4, and 5; Grade B: sticking to examples 1, 6, 7, 8, and 9;

[0093] The unwinding force test results of the annealing rack (6) are as follows: Grade A: Examples 1, 2, 4, and 6 are adhered; Grade B: Examples 3, 5, 7, 8, and 9 are adhered.

[0094] After taking the cost into consideration, the internal addition of 10% is already the cost limit of the film. According to the customer's usage habits, Class B unwinding is also acceptable. If better unwinding effect or higher viscosity products are required, the surface EXfo la additive can be removed, and the release can be achieved by coating the surface with silicone oil and then curing. The equipment can be equipped with silicone-coated curing parts to meet production needs.

[0095] The above description is only the preferred embodiment of the present invention, which does not limit the protection scope of the present invention. For those skilled in the art, the present invention can be modified and varied in various ways. Within the spirit and principle of the present invention, any change, modification, replacement, integration and parameter change of these embodiments by conventional substitution or capable of achieving the same function without departing from the principle and spirit of the present invention shall fall within the protection scope of the present invention.

Claims

1. A multi-layer co-extruded one-step self-adhesive ultra-thin foam cotton tape, characterized in that: It includes an antistatic release layer, a foaming layer, a bonding layer and an adhesive layer, wherein the antistatic release layer, the foaming layer and the bonding layer are collectively referred to as a substrate layer; The antistatic release layer is composed of LDPE, Exfola and antistatic masterbatch; The foaming layer is composed of LLDPE, LDPE, edge material and foaming masterbatch; The bonding layer is composed of LDPE and SEBS; The adhesive layer is composed of SEBS, tackifying resin, white oil, fumed silica and antioxidant; The component ratio of the antistatic release layer is: 85% LDPE, 10% Exfola, and 5% antistatic masterbatch; The component ratio of the foaming layer is: 65% LLDPE, 20% LDPE, 10% edge material, and 5% foaming masterbatch; The component ratio of the bonding layer is: 95% LDPE and 5% SEBS.

2. A multi-layer co-extruded one-step self-adhesive ultra-thin foamed cotton tape as claimed in claim 1, characterized in that: The component ratio of the adhesive layer is: 30 parts SEBS, 40-60 parts tackifying resin, 10-20 parts white oil, 1 part fumed silica, and 0.5 parts antioxidant.

3. A multi-layer co-extruded one-step self-adhesive ultra-thin foamed cotton tape as claimed in claim 2, characterized in that: The particle size of the foaming masterbatch is selected to be 28-40 μm, the starting temperature is 165-175° C., and the maximum temperature is 215-225° C.

4. A method for preparing a multi-layer co-extruded one-step self-adhesive ultra-thin foamed cotton tape, characterized in that: All the formulation materials of the adhesive layer are made into granules in advance by a granulator, using a double-stage underwater granulation system, and different weight loss scale systems are used for each component.

5. The preparation method according to claim 5, characterized in that: The white oil is added by a special liquid scale and injected into the screw at the second heating zone, and the remaining materials are discharged conventionally at the first discharge port.

6. The preparation method according to claim 6, characterized in that: The components of the adhesive layer are prepared in advance as adhesive layer master batches, and the equipment required for preparing the adhesive layer master batches includes a first granulator, a double cone feeder, and a second granulator; The preparation method of the adhesive layer masterbatch comprises the following steps: S1): 30 components of SEBS, 40-60 components of tackifying resin, 10-20 components of white oil, 0.5 components of fumed silica, and 0.5 components of antioxidant are put into use in a first granulator at a granulation temperature of 120-160 degrees to prepare a semi-finished tack layer masterbatch; S2): The semi-finished adhesive masterbatch obtained in S1 is put into a double cone feeder, and the double cone feeder side force feeding method is used to vertically feed the discharge port of the double cone feeder into the feed port of the second single screw granulator at 90 degrees; S3): Use the second granulator with a screw temperature of 80-100 degrees to prepare the sticky masterbatch, and the remaining 0.5 component of fumed silica is sprinkled on the molded particles as an anti-sticking release agent to prevent adhesion.

7. The preparation method according to claim 6, characterized in that: The first granulator is preferably a co-rotating three-screw device with an aspect ratio greater than 68; the second granulator is preferably a "high compression ratio" machine with a single screw diameter greater than 100 mm and an aspect ratio greater than 48.

8. The preparation method according to claim 8, characterized in that: The first granulator adopts the first stage natural exhaust, the second stage vacuuming to treat volatiles, and the second stage adopts the natural exhaust method to form.

9. The preparation method according to claim 8, characterized in that: The foam tape is prepared using a four-layer co-extrusion integral rotary film blowing device, the four-layer co-extrusion integral rotary film blowing device comprising a die head (1), an extruder (2), a winding mechanism (3), a thickness gauge (4), a cooling roller (5), an annealing frame (6), an infrared heating mechanism (7), an edge material winding mechanism (8), a traction mechanism (9), an edge trimming mechanism (10), a herringbone frame (11), a foam stabilizing frame (12) and a five-layer frame, wherein the five-layer frame is divided into a bottom layer, a first layer, a second layer, a third layer and a fourth layer; The number of the extruders (2) is four, which are divided into ABCD extruders. The die head (1) is installed in the middle of the bottom layer. The four extruders (2) are installed around the bottom layer. The discharge end of the extruder (2) is connected to the feed end of the die head (1). The winding mechanism (3) is installed on both sides of the first layer. The thickness gauge (4) is installed on both sides of the second layer. The bubble stabilizing frame (12) is installed in the middle of the second layer. The annealing frame (6) and the winding mechanism (3) are installed on both sides of the third layer. The traction mechanism (9) and the herringbone frame (11) are installed in the middle of the third layer. The trimming mechanism (10) and the edge material winding mechanism (8) are installed in the middle of the fourth layer. The infrared heating mechanism (7) is installed on both sides of the fourth layer.

10. The preparation method according to claim 9, characterized in that: The adhesive layer masterbatch is added to a single-screw mold machine and extruded into a film at a temperature of about 100-120 degrees. The raw materials of the antistatic release layer, foaming layer, and bonding layer are respectively put into the corresponding ABC extruder for extrusion into a film. The processing temperature is 190 degrees, and the film frost line height is 50-120cm. By adjusting the screw speed, composite extrusion is performed at a ratio of 20% for the adhesive layer and 80% for the substrate layer. After hot air shaping, a 110um thick thin film self-adhesive tape is produced.

Citation Information

Patent Citations

  • Preparation method of light-shading foam tape

    CN108084909A

  • Double-sided composite ultrahigh-viscosity self-adhesive film, production process and equipment

    CN119286418A